2017
DOI: 10.37922/pijmit.2017.v06i01.010
|View full text |Cite
|
Sign up to set email alerts
|

Physical Environment and Employee Behaviour Shape Consumer Perciption in Restaurant

Abstract: Financial inclusion is the apparatus of ensuring access to financial services along with timely and adequate credit whenever needed by the vulnerable groups at an affordable cost. India, a growing economy has special significance of financial inclusion as it brings large disadvantaged sections of the society under financial ambit. Post offices as banks offered a trustworthy and extensive network that was directly accessible to scattered rural communities. This access to financial services generates income, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Financial inclusion plays a crucial role in promoting economic empowerment, particularly among marginalized communities and women. Studies have shown a positive relationship between financial inclusion and economic empowerment (Lal, 2021;Aziz et al, 2022;Jedi, 2022;Siddik, 2017;Pal et al, 2021;Bhakar, 2017;Manta, 2019). Financial inclusion not only provides access to financial services but also contributes to social and economic empowerment.…”
Section: Relationship Between Financial Inclusion and Economic Empowe...mentioning
confidence: 99%
See 2 more Smart Citations
“…Financial inclusion plays a crucial role in promoting economic empowerment, particularly among marginalized communities and women. Studies have shown a positive relationship between financial inclusion and economic empowerment (Lal, 2021;Aziz et al, 2022;Jedi, 2022;Siddik, 2017;Pal et al, 2021;Bhakar, 2017;Manta, 2019). Financial inclusion not only provides access to financial services but also contributes to social and economic empowerment.…”
Section: Relationship Between Financial Inclusion and Economic Empowe...mentioning
confidence: 99%
“…Financial inclusion not only provides access to financial services but also contributes to social and economic empowerment. It has been found that financial inclusion leads to increased economic opportunities for low-income individuals, resulting in positive outcomes in social progress, economic development, and empowerment (Bhakar, 2017). Moreover, financial inclusion initiatives have been linked to supporting women's economic empowerment by enabling them to address challenges, provide better education for their children, access healthcare, and gain independence (Pal et al, 2021;Arshad, 2023;Yakubi et al, 2020).…”
Section: Relationship Between Financial Inclusion and Economic Empowe...mentioning
confidence: 99%
See 1 more Smart Citation